Biochemical Evaluation and Green Synthesis of Nano Silver Using Peroxidase from Euphorbia (Euphorbia amygdaloides) and Its Antibacterial Activity - Semra Cicek; Azize Alaylı Gungor; Ahmet Adiguzel; Hayrunnisa Nadaroglu (Journal of Chemistry)
Silver nanoparticles are used an increased attention for various biomedical and medical applications. In this study, green synthesis of silver nanoparticles was made with simple method by using peroxidase enzyme partially purified from Euphorbia (Euphorbia amygdaloides) plant. Optimum pH, temperature and time period were determined to obtain silver nanoparticles using the peroxidase enzyme. The result shows that higher silver nanoparticle was synthesized for 4 hours and at 20°C and pH 8. Also, optimal concentration of metal ions was found as 0.5 mM. The synthesized silver nanoparticles were characterized by UV spectrum, scanning electron microscope (SEM) and X-ray diffraction. Antibacterial activity of silver nanoparticles was measured against some microorganisms such as Serratia marcescens, Yersinia pseudotuberculosis, Klebsiella pneumoniae, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Pseudomonas aeruginosa, Salmonella typhimurium, Listeria monocytogenes, and Escherichia coli. Synthesized silver nanoparticles have wide spectrum antibacterial activity in low concentration and may be a good alternative therapeutic approach in medicine and pharmaceutical fields in future.